2011
DOI: 10.1186/1745-6215-12-148
|View full text |Cite
|
Sign up to set email alerts
|

A post-trial survey to assess the impact of dissemination of results and unmasking on participants in a 13-year randomised controlled trial on age-related cataract

Abstract: BackgroundThe Italian-American Clinical Trial of Nutritional Supplements and Age-Related Cataract was designed to assess the impact of a multivitamin-mineral supplement on age-related cataract. Trial results showed evidence of a beneficial effect of the supplement on all types of cataract combined, opposite effects on two of the three types of cataract (beneficial for nuclear opacities and harmful for posterior sub-capsular opacities) and no statistically significant effect on cortical opacities. No treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…A questionnaire survey of participants’ reactions to receiving the results leaflet was conducted. Aggregate Not specified Locock 2011 [ 26 ] Personal experiences of taking part in clinical trials—a qualitative study Trial participants 42 27 female; 15 male 38-84 years N/A UK To investigate people’s experiences of and attitudes to participation in clinical trials interviews N/A N/A Williams 2011 [ 27 ] The Italian-American Clinical Trial of Nutritional supplements and Age-Related Cataract (CTNS) Trial participants 610 46.7% female; 53.3% male Mean age 80.5 Not specified Italy To determine whether participants were satisfied with the trial results. Survey Aggregate and individual After publication Darbyshire 2012 [ 28 ] Disseminating results to clinical trial participants: a qualitative review of patient understanding in a post-trial population Trial participants 40 Not specified Not specified Secondary care UK To identify the most appropriate format for results dissemination to maximise understanding of trial results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A questionnaire survey of participants’ reactions to receiving the results leaflet was conducted. Aggregate Not specified Locock 2011 [ 26 ] Personal experiences of taking part in clinical trials—a qualitative study Trial participants 42 27 female; 15 male 38-84 years N/A UK To investigate people’s experiences of and attitudes to participation in clinical trials interviews N/A N/A Williams 2011 [ 27 ] The Italian-American Clinical Trial of Nutritional supplements and Age-Related Cataract (CTNS) Trial participants 610 46.7% female; 53.3% male Mean age 80.5 Not specified Italy To determine whether participants were satisfied with the trial results. Survey Aggregate and individual After publication Darbyshire 2012 [ 28 ] Disseminating results to clinical trial participants: a qualitative review of patient understanding in a post-trial population Trial participants 40 Not specified Not specified Secondary care UK To identify the most appropriate format for results dissemination to maximise understanding of trial results.…”
Section: Resultsmentioning
confidence: 99%
“… Postal Informed by the findings of the focus groups and input from other stakeholders, a results leaflet for participants was produced, and an integrated process of feedback and support was developed. Not reported Not specified Not specified Locock 2011 [ 26 ] N/A N/A N/A N/A Not reported N/A N/A Williams 2011 [ 27 ] Aggregate and individual The frequency figures were used to demonstrate the effect of treatment. The letter indicated that, because of the qualitatively different effect of treatment on the different types of cataract, the investigators could not recommend regular use of the supplement for the prevention of cataract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other studies of participants' views of unblinding [3,5], our interviews were not linked to an explicit offer to unblind participants as to their treatment allocation. As a result, the women in this study were not discussing their actual experiences of being unblinded (or choosing not to be), but rather the possibility of finding out their treatment allocation more generally.…”
Section: Discussionmentioning
confidence: 99%
“…The limited evidence to date suggests that trial participants generally want to be unblinded to treatment allocation on trial completion, and that few patients report concerns at finding out to which trial arm they were allocated [3,5]. But in trials where analysis reveals adverse outcomes for some participant groups, the possible unblinding of participants may be less straightforward.…”
Section: Introductionmentioning
confidence: 99%